KERJA SAMA MEMODERASI PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA STRATEGIC SUPPLY RELATIONSHIP (STUDI KASUS RUMAH SAKIT DI KOTA PALEMBANG - Nafsiah, Siti Nurhayati (Fakultas Ekonomi Universitas IBA, 2019)
This research is a model that tests the effect of performance measurement systems on role clarity,psychological empowerment and managerial performance. This research was conducted at ahospital in the city of Palembang, with a sample of 55 managers. Data collected fromquestionnaires were delivered directly to the object of the research and tested through SEM usingAMOS. The test results show that the Management Control System has a positive and negativeeffect on cooperation, Management Control Systems have a positive and negative effect on SSRsPerformance, Management Control Systems have positive and negative effects on SSRsPerformance with collaboration and communication as moderating variables. That way theManagement Control System effectiveness afects the performance of SSRs.